Gradient composite brazing filler metal and preparation method and application thereof
By designing a gradient composite brazing filler metal and using Ag-Cu-Zn-Sn and Cu-Zn-Ni alloy layers to form a low-temperature welding structure, the problem of excessively high welding temperature of GH4169D alloy was solved, achieving a welding effect with high strength and low damage.
Patent Information
- Application Number
- CN202511686117.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2025-12-19
AI Technical Summary
When existing nickel-based and titanium-based brazing filler metals are used for welding GH4169D alloy, excessively high temperatures cause the η phase to dissolve, reducing the alloy's crack resistance and notch sensitivity.
A gradient composite brazing filler metal, including an Ag-Cu-Zn-Sn alloy layer and a Cu-Zn-Ni alloy layer, is used to form Cu-based solid solution and Ni-based solid solution microstructures through low-temperature welding, thereby reducing the welding temperature and improving the joint strength.
Low-temperature and high-efficiency welding of GH4169D alloy was achieved, significantly reducing the risk of thermal damage, improving joint reliability and strength, and avoiding the dissolution problem of the η phase.
Smart Images

Figure CN121156578A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-temperature alloy welding materials and processes, and more specifically, to a gradient composite brazing filler metal, its preparation method, and its application. Background Technology
[0002] GH4169D is an age-hardening nickel-based superalloy developed based on GH4169. GH4169 is primarily strengthened by the γ′′ phase, with the γ′ phase playing a secondary role, and a δ phase exists at the grain boundaries. By controlling the content of Co and W elements and reducing the Fe content, while adjusting the Al, Ti, and Nb, the precipitation of the γ′′ phase in the alloy is suppressed. This transforms the metastable γ′′ phase in GH4169D into a stable γ′ phase, which is the main strengthening phase. Simultaneously, it delays the coarsening of the γ′ phase at high temperatures, improving its thermal stability and high-temperature mechanical properties. GH4169D has a service temperature 55 °C higher than GH4169 and retains the advantages of GH4169 alloy, such as good hot workability, weldability, and low cost. It is considered a good candidate material for important components such as turbine disks, compressor disks, housings, and fasteners in advanced aero-engines. The grain boundary precipitates in GH4169D were initially thought to be δ-Ni3Nb, but were later confirmed to be η-Ni6AlNb. The η phase is a discontinuous precipitate that precipitates in needle-like forms at grain boundaries, pinning these boundaries, hindering crack propagation, and preventing notch sensitivity. After standard heat treatment, the mass fraction of the η phase in the alloy is 1.5%-7%. Too low a content will exacerbate the notch sensitivity of the alloy; its content should not be lower than 1.1%. When the η phase content is approximately 2.5%, the alloy exhibits good overall properties. However, the melting temperature of the η phase is below 1020 °C, and controlling the welding temperature to ensure an appropriate amount of η phase in the base metal is a key issue in welding GH4169D. Currently, commonly used brazing filler metals for nickel-based superalloys include nickel-based and titanium-based filler metals, with welding temperatures generally exceeding 1020 °C. Therefore, developing a proprietary low-temperature filler metal more suitable for brazing GH4169D alloy and achieving highly reliable connections of GH4169D alloy has become an urgent technical problem to be solved.
[0003] In view of this, the present invention is hereby proposed. Summary of the Invention
[0004] The primary objective of this invention is to provide a gradient composite brazing filler metal that can be used for low-temperature brazing of GH4169D alloy, solving the problem that the η phase in the alloy dissolves due to excessively high brazing temperatures caused by traditional Ni-based and Ti-based brazing filler metals.
[0005] The second objective of this invention is to provide a method for preparing the gradient composite solder as described above.
[0006] A third objective of this invention is to provide an application of the gradient composite brazing filler metal described above in welding nickel-based superalloys.
[0007] The fourth objective of this invention is to provide a welding method for GH4169D alloy, which uses the gradient composite brazing filler metal as described above for brazing. The brazing temperature of this method is lower than the dissolution temperature of the η phase in the alloy, and the prepared GH4169D welded joint has no macroscopic defects such as cracks and voids, and the joint has high shear strength.
[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: A gradient composite solder includes a first alloy layer, a second alloy layer and a third alloy layer stacked sequentially, wherein the first alloy layer and the third alloy layer are both Ag-Cu-Zn-Sn alloys and the second alloy layer is a Cu-Zn-Ni alloy; The Ag-Cu-Zn-Sn alloy comprises, by mass percentage, 35%–45% Cu, 30%–40% Zn, 0.5%–5% Sn, with Ag as the balance. The Cu-Zn-Ni alloy comprises 35%~39% Zn, 1%~9% Ni, and the balance Cu, based on atomic percentage.
[0009] Preferably, the total thickness of the gradient composite solder is 180-260µm.
[0010] Preferably, the thickness ratio of the first alloy layer, the second alloy layer and the third alloy layer is 5~8:8~10:5~8.
[0011] A method for preparing a gradient composite solder according to any one of the foregoing embodiments includes the following steps: S1. Using Ag, Cu, Zn, and Sn as raw materials, alloy blocks are prepared by melting and casting, and then processed into foil to obtain a first alloy foil and a third alloy foil; using Cu, Zn, and Ni as raw materials, alloy blocks are prepared by melting and casting, and then processed into foil to obtain a second alloy foil; S2. The first alloy foil, the second alloy foil, and the third alloy foil are combined together in the order of "first alloy foil-second alloy foil-third alloy foil" to obtain a three-layer gradient structure.
[0012] Preferably, in step S1, the processing steps include rolling and / or wire cutting, and also include grinding.
[0013] Preferably, in step S1, the thickness of the first alloy foil and the third alloy foil is 50~80μm.
[0014] Preferably, in step S1, the thickness of the second alloy foil is 80~100µm.
[0015] Preferably, in step S2, the composite process is a resin bonding process.
[0016] Application of the gradient composite brazing filler metal as described in any of the preceding embodiments or the brazing filler metal prepared by the method described in any of the preceding embodiments in welding nickel-based superalloys.
[0017] A welding method for GH4169D alloy includes the following steps: The GH4169D alloy and brazing material are assembled in the order of "GH4169D alloy-brazing material-GH4169D alloy" to obtain an assembly, and then vacuum brazing is performed. The brazing material is either the gradient composite brazing alloy as described in any of the preceding embodiments or the brazing alloy prepared by the method described in any of the preceding embodiments.
[0018] Preferably, the vacuum brazing process includes: first, evacuating the vacuum, then heating the temperature to 350~450℃ at a first heating rate, then applying a preload of 8~12MPa to the assembly for a first heat preservation; after the heat preservation is completed, reducing the load to 4~6MPa, heating the temperature to the welding temperature at a second heating rate, and performing a second heat preservation; after the heat preservation is completed, removing the pressure and cooling.
[0019] Preferably, the first heating rate is 8~12℃ / min; and / or, the second heating rate is 8~12℃ / min.
[0020] Preferably, the first heat preservation time is 20-40 minutes; and / or, the second heat preservation time is 30-60 minutes.
[0021] Preferably, the welding temperature of the vacuum brazing is 860~890℃.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The gradient composite brazing alloy provided by the present invention comprises a three-layer structure, with low-melting-point Ag-Cu-Zn-Sn alloy on both sides and Cu-Zn-Ni alloy in the middle transition layer. It can realize low-temperature and high-efficiency welding of GH4169D alloy, significantly reducing the welding temperature. It solves the problem that the brazing temperature is too high when brazing GH4169D alloy with Ni-based brazing alloy and Ti-based brazing alloy, which leads to the dissolution of the η phase in the base material, thereby reducing the crack resistance and notch sensitivity of the base material. Moreover, the preparation process of the gradient composite brazing alloy is simple and low-cost.
[0023] (2) This invention uses the brazing filler metal composition and structural design in conjunction with the stepped pressure process to make the weld seam form a microstructure mainly composed of Cu-based solid solution and Ni-based solid solution. It achieves ultra-high strength connection under conditions lower than the η phase transformation temperature of GH4169D alloy, breaks through the high temperature limitation of traditional Ni-based brazing filler metal and Ti-based brazing filler metal, and achieves low-temperature and high-efficiency welding through gradient composite structure, which significantly reduces the risk of thermal damage and the prepared joint has high reliability. Attached Figure Description
[0024] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0025] Figure 1 This is a microstructure diagram of the GH4169D alloy welded joint prepared in Example 1 of the present invention. Detailed Implementation
[0026] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0027] The first aspect of the present invention provides a gradient composite solder, comprising a first alloy layer, a second alloy layer and a third alloy layer stacked sequentially, wherein the first alloy layer and the third alloy layer are both Ag-Cu-Zn-Sn alloys and the second alloy layer is a Cu-Zn-Ni alloy; wherein the composition of the first alloy layer and the third alloy layer may be the same or different, preferably the same; By mass percentage, the Ag-Cu-Zn-Sn alloy comprises 35%–45% Cu, 30%–40% Zn, 0.5%–5% Sn, with the balance being Ag. Typically, but not limitingly, for example, the mass percentage of Cu can be any single value or a range of any two values from 35%, 37%, 40%, 42%, and 45%; the mass percentage of Zn can be any single value or a range of any two values from 30%, 32%, 35%, 38%, and 40%; and the mass percentage of Sn can be any single value or a range of any two values from 0.5%, 1%, 2%, 3%, 4%, and 5%. Based on atomic percentage, Cu-Zn-Ni alloys comprise 35%–39% Zn, 1%–9% Ni, and the balance Cu. Typically, but not limitingly, the atomic percentage of Zn can be any single value or a range of any two values from 35%, 36%, 37%, 38%, and 39%; the atomic percentage of Ni can be any single value or a range of any two values from 1%, 3%, 5%, 7%, and 9%. Controlling the elemental content within these ranges promotes the maximum formation of Cu-based solid solution in the brazing seam.
[0028] The gradient composite brazing alloy provided by this invention comprises a three-layer structure, with low-melting-point Ag-Cu-Zn-Sn alloys on both sides and a Cu-Zn-Ni alloy in the middle transition layer. It is suitable for low-temperature and high-efficiency welding of GH4169D alloy, with a welding temperature lower than the η-phase dissolution temperature of GH4169D alloy. This solves the problem that when using traditional Ni-based and Ti-based brazing alloys to braze GH4169D alloy, the brazing temperature is too high, leading to the dissolution of the η-phase in the base material, which in turn reduces the crack resistance and notch sensitivity of the base material.
[0029] During brazing, the Ag-Cu-Zn-Sn alloys with lower melting points on both sides of the filler metal melt first to form a liquid phase, which fills the joint gap through capillary action. The Cu-Zn-Ni alloy in the middle layer, with a higher melting point, remains solid and interdiffusion with the molten low-melting-point filler metal through the dissolution effect to form a solid solution. Finally, a brazed joint structure with Cu-based solid solution and Ni-based solid solution as the main microstructure is formed. This can significantly reduce the brazing temperature, break through the high temperature limit of traditional Ni-based and Ti-based filler metals, significantly reduce the risk of thermal damage, and improve the reliability of the joint.
[0030] In some specific embodiments of the present invention, the total thickness of the gradient composite solder is 180-260µm. For example, it can be any one value or a range of any two values among 180µm, 200µm, 220µm, 240µm, and 260µm.
[0031] In some specific embodiments of the present invention, the thickness ratio of the first alloy layer, the second alloy layer, and the third alloy layer is 5~8:8~10:5~8. For example, it can be any one value or a range of any two values from 5:8:5, 5:9:5, 5:10:5, 7:8:7, 7:9:7, 7:10:7, 8:9:8, 8:10:8. The thicknesses of the first alloy layer and the third alloy layer can be the same or different, preferably the same. Preferably, the thicknesses of the first alloy layer and the third alloy layer are lower than the thickness of the second alloy layer, thereby reducing the Ag-based solid solution phase in the brazing seam.
[0032] A second aspect of the present invention provides a method for preparing a gradient composite solder as described in any of the foregoing embodiments, comprising the following steps: S1. Using Ag, Cu, Zn, and Sn as raw materials, Ag-Cu-Zn-Sn alloy blocks are prepared by melting and casting, and then processed into foil to obtain a first alloy foil and a third alloy foil; using Cu, Zn, and Ni as raw materials, Cu-Zn-Ni alloy blocks are prepared by melting and casting, and then processed into foil to obtain a second alloy foil; S2. The first alloy foil, the second alloy foil, and the third alloy foil are combined together in the order of "first alloy foil-second alloy foil-third alloy foil" to obtain a three-layer gradient structure, which is the gradient composite solder. The order in which the first alloy foil, the second alloy foil, and the third alloy foil are prepared is not limited; any one or two of them can be prepared first, or all three can be prepared simultaneously.
[0033] The method for preparing the gradient composite brazing filler metal of this invention is simple, easy to implement, and low in cost. When the prepared brazing filler metal is used to weld GH4169D alloy joints, the welding temperature is low and the joint strength is high.
[0034] In some specific embodiments of the present invention, step S1, the method for preparing the alloy block specifically includes the following steps: S101. Weigh the metal raw materials according to the alloy composition ratio; S102. The metal raw material is ultrasonically cleaned with anhydrous ethanol and then dried; S103. High-frequency induction melting process is used to melt metal raw materials under the protection of a covering agent (such as FB102S) to obtain alloy liquid; S104. Pour the molten alloy into a mold, cool and demold to obtain an alloy block.
[0035] The purpose of ultrasonic cleaning in step S102 is to remove oil stains from the surface of metal particles. In step S103, the ultrasonically cleaned metal raw material is placed at the bottom of the crucible, and a covering agent is distributed on the surface of the metal particles. During the high-frequency induction melting process, the covering agent melts first to cover the surface of the molten pool to form a protective layer to isolate the air. A special carbon rod is used to slowly stir to promote the homogenization of the composition and accelerate the floating of oxides. A graphite carbon rod is used to stir and remove slag.
[0036] In some specific embodiments of the present invention, step S1, the processing steps of processing the alloy block into alloy foil include rolling and / or wire cutting, and also grinding; as an example, the Ag-Cu-Zn-Sn alloy block is prepared into a strip-shaped intermediate layer by rolling, and then ground to obtain a first alloy foil and a third alloy foil of the required thickness; the Cu-Zn-Ni alloy block is processed into a sheet by wire cutting and ground to the required thickness to obtain a second alloy foil.
[0037] In some specific embodiments of the present invention, in step S1, the thickness of the first alloy foil and the third alloy foil are independently controlled to be 50~80μm. For example, they can be independently selected from any one value or a range of any two values among 50μm, 60μm, 70μm, and 80μm.
[0038] In some specific embodiments of the present invention, in step S1, the thickness of the second alloy foil is 80~100µm. For example, it can be any one value or a range of any two values among 80µm, 85µm, 90µm, 95µm, and 100µm.
[0039] In some specific embodiments of the present invention, in step S2, the composite process is a resin bonding process; as an example, the bonding resin used can be polyvinyl alcohol resin.
[0040] The third aspect of the present invention provides the application of a gradient composite brazing filler metal as described in any of the foregoing embodiments or a brazing filler metal prepared by the method described in any of the foregoing embodiments in welding nickel-based superalloys, for example, in welding GH4169D alloy.
[0041] The gradient composite brazing filler metal provided by this invention can be used for brazing nickel-based superalloys, especially suitable for brazing GH4169D alloy. Currently, the commonly used brazing filler metals for nickel-based superalloys in the prior art are nickel-based and titanium-based filler metals, with welding temperatures generally higher than 1020℃. This causes the η phase in GH4169D alloy to dissolve, resulting in a decrease in the crack resistance and notch sensitivity of the base metal, and therefore it is not suitable for brazing GH4169D alloy. However, the gradient composite brazing filler metal provided by this invention has a welding temperature lower than the dissolution temperature of the η phase in GH4169D alloy, which can achieve low-temperature and high-efficiency welding of GH4169D alloy, which can not only improve the joint strength, but also reduce energy consumption.
[0042] A fourth aspect of the present invention provides a welding method for GH4169D alloy, comprising the following steps: The GH4169D alloy and brazing material are assembled in the order of "GH4169D alloy-brazing material-GH4169D alloy" to obtain an assembly, and then vacuum brazing is performed. The brazing material used is either the gradient composite brazing alloy as described in any of the preceding embodiments or the brazing alloy prepared by the method described in any of the preceding embodiments.
[0043] This invention employs a gradient composite brazing filler metal formed by combining a low-melting-point Ag-Cu-Zn-Sn alloy with a Cu-Zn-Ni alloy to weld GH4169D alloy. During the welding process, the Ag-Cu-Zn-Sn alloys on both sides melt first to form a liquid phase, which fills the joint gap through capillary action. The Cu-Zn-Ni alloy in the middle remains solid, forming a brazing seam structure with Cu-based solid solution and Ni-based solid solution as the main microstructures through the dissolution effect. This significantly reduces the welding temperature, making it lower than the dissolution temperature of the η phase in the base metal. This overcomes the high-temperature limitations of traditional nickel-based and titanium-based brazing filler metals, reduces the risk of thermal damage, and improves joint reliability.
[0044] In some specific embodiments of the present invention, vacuum brazing employs a transient liquid phase diffusion welding method, the specific process including: (1) Place the assembly in a vacuum furnace and first evacuate the vacuum furnace (≤6×10). -3 Pa); (2) Then heat the assembly to 350~450℃ at the first heating rate, and then apply a preload of 8~12MPa to the assembly for the first heat preservation. (3) After the first heat preservation is completed, the load is reduced to 4~6MPa, and the temperature is raised to the welding temperature at the second heating rate for the second heat preservation. (4) After the second heat preservation is completed, the pressure is removed and the furnace is cooled to room temperature to complete the welding, thus obtaining the GH4169D alloy welded joint.
[0045] This invention employs a stepped pressure reduction welding process. A higher preload is applied at low temperatures to promote interfacial micro-deformation and element interdiffusion; the load is reduced at high temperatures to avoid joint strength reduction or failure due to base material deformation. Using a low pressure load throughout the welding process would affect element interdiffusion, leading to reduced joint strength; conversely, using a high pressure load throughout the welding process, especially at high temperatures, would cause thermal base material deformation, reducing joint strength and potentially leading to joint failure. The welding process of this invention achieves excellent welding results, with no macroscopic defects such as cracks or voids in the weld seam, which is mainly composed of nickel-based and copper-based solid solutions, and a joint strength reaching 708 MPa.
[0046] In some embodiments, typically but not limitingly, for example, the temperature of the first insulation can be any one value or a range of any two values from 350°C, 380°C, 400°C, 420°C, and 450°C; the preload applied during the first insulation stage can be any one value or a range of any two values from 8MPa, 9MPa, 10MPa, 11MPa, and 12MPa; and the pressure load applied during the second insulation stage can be any one value or a range of any two values from 4MPa, 4.5MPa, 5MPa, 5.5MPa, and 6MPa.
[0047] In some specific embodiments of the present invention, the first heating rate is 8~12℃ / min; and / or, the second heating rate is 8~12℃ / min; for example, the first heating rate and the second heating rate can be independently selected from any one value or a range of any two values among 8℃ / min, 9℃ / min, 10℃ / min, 11℃ / min, and 12℃ / min.
[0048] In some specific embodiments of the present invention, the first heat preservation time is 20 to 40 minutes, for example, it can be any one value or a range of any two values among 20 minutes, 25 minutes, 30 minutes, 35 minutes, and 40 minutes; and / or, the second heat preservation time is 30 to 60 minutes, for example, it can be any one value or a range of any two values among 30 minutes, 40 minutes, 50 minutes, and 60 minutes.
[0049] In some specific embodiments of the present invention, the welding temperature of vacuum brazing is 860~890℃, for example, it can be any one value or a range of any two values among 860℃, 870℃, 880℃, and 890℃. If the welding temperature is too high or too low, the joint strength will be reduced. The welding temperature in the present invention can achieve good metallurgical bonding and is lower than the dissolution temperature of the η phase in the GH4169D alloy, which can avoid the dissolution of the η phase due to excessive welding temperature.
[0050] The embodiments of the present invention will be described in detail below with reference to specific examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0051] Example 1 This embodiment provides a gradient composite solder, comprising a first alloy layer, a second alloy layer, and a third alloy layer stacked sequentially. The first and third alloy layers are Ag30Cu37Zn32Sn alloys (composed of Ag 30%, Cu 37%, Zn 32%, and Sn 1% by mass percentage), each with a thickness of 80 μm. The second alloy layer is Cu... 54 Zn 37 Ni9 alloy (at.%), thickness 100 μm; The preparation steps are as follows: S1. Prepare a first alloy foil, a second alloy foil, and a third alloy foil; (a) Preparation of alloy blocks S101. Using a precision electronic scale, weigh the Ag, Cu, Zn, and Sn metal particles according to their alloy composition and mass percentage ratio; S102. Place the weighed 30 g of metal particles (total weight of 4 metal particles) in anhydrous ethanol and use an ultrasonic cleaner to perform ultrasonic cleaning for 10 min to remove oil stains and then place it in a vacuum drying oven for drying. S103. Place the cleaned and dried metal particles at the bottom of the crucible, and use 5 g of FB102S as a covering agent on the surface of the metal particles. Turn on the high-frequency induction heating equipment for melting. During the melting process, use a carbon rod to stir for 30 seconds to promote the homogenization of the alloy composition and accelerate the floating of oxides. At the same time, use a graphite carbon rod to stir and remove slag to obtain an alloy liquid. S104. Pour the molten alloy solution into a mold, cool and demold to prepare a 40mm×40mm×5mm Ag-Cu-Zn-Sn alloy block; According to Cu 54 Zn 37 The Ni9 alloy was prepared using the steps described above to prepare Cu-Zn-Ni alloy blocks; (b) Preparation of alloy foil Ag-Cu-Zn-Sn alloy blocks were rolled into strip-shaped intermediate layers with a thickness of 200 μm and then ground to 80 μm with 400-mesh SiC sandpaper to obtain the first alloy foil and the third alloy foil. The Cu-Zn-Ni alloy block was processed into a sheet by wire cutting and then ground to a thickness of 70μm using 400-mesh SiC sandpaper to obtain the second alloy foil. S2. The first alloy foil, the second alloy foil, and the third alloy foil are bonded together using polyvinyl alcohol resin to obtain a gradient composite solder with a thickness of 230 μm.
[0052] Example 2 Example 2 is similar to Example 1, except that the second alloy layer is Cu. 56 Zn 37 Ni7 alloy (at.%), all other conditions were the same as in Example 1.
[0053] Application Example 1 Vacuum brazing of GH4169D / gradient composite brazing filler metal / GH4169D joints, using the gradient composite brazing filler metal prepared in Example 1, the specific steps are as follows: (1) Assemble GH4169D alloy and gradient composite brazing filler metal in the form of “GH4169D - gradient composite brazing filler metal - GH4169D” to obtain an assembly; (2) Place the assembly in a vacuum furnace, and reduce the vacuum level to 6×10 before heating begins. -3 Below Pa; (3) Heat the brazing furnace to 400°C at a heating rate of 10°C / min, apply a preload of 10MPa to the assembly, and hold for 30 min to promote micro-deformation of the interface and interdiffusion of elements. (4) After the heat preservation is completed, the load is reduced to 5MPa by dynamic pressure control, and then the temperature is increased to the target welding temperature of 890℃ at 10℃ / min, and the temperature is maintained for 30min. (5) After the heat preservation is completed, the sample is cooled to room temperature in the furnace and then taken out.
[0054] Application Example 2 Application Example 2 is similar to Application Example 1, except that: Application Example 2 uses the gradient composite brazing filler metal prepared in Example 2, the target welding temperature in step (4) is 870°C, and the other conditions are similar to those in Application Example 1.
[0055] Comparative Example 1 Comparative Example 1 is similar to Application Example 1, except that the target welding temperature in step (4) is 910°C, and all other conditions are the same as in Application Example 1.
[0056] Comparative Example 2 Comparative Example 2 is similar to Application Example 1, except that the target welding temperature in step (4) is 850°C, and all other conditions are the same as in Application Example 1.
[0057] Comparative Example 3 Comparative Example 3 is similar to Application Example 1, except that the loads in steps (3) and (4) are both 5 MPa, and the other conditions are the same as in Application Example 1.
[0058] Comparative Example 4 Comparative Example 4 is similar to Application Example 1, except that the loads in steps (3) and (4) are both 10 MPa, and the other conditions are the same as in Application Example 1.
[0059] Comparative Example 5 The solder used is similar to the gradient composite solder in Example 1, except that the thickness of the first alloy layer is 80 μm, the thickness of the second alloy layer is 75 μm, and the thickness of the third alloy layer is 80 μm. The welding process is the same as in Application Example 1.
[0060] Comparative Example 6 Comparative Example 6 is similar to Application Example 1, except that: Comparative Example 6 uses the first alloy layer prepared in Example 1 as the Ag30Cu37Zn32Sn solder, and the thickness is the same as the total thickness of the three alloy layers in Example 1; all other conditions are the same as in Application Example 1.
[0061] Test case According to GB / T 11363, the joint shear strength in each application example and comparative example was tested, and the metallographic morphology of the weld in application example 1 was observed. The test results are shown in Table 1.
[0062] Table 1
[0063] Depend on Figure 1 It is known that the joints brazed using the gradient composite brazing filler metal and welding method of this invention have no macroscopic defects such as cracks and voids.
[0064] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.
Claims
1. A gradient composite filler material, characterized by, The gradient composite filler comprises a first alloy layer, a second alloy layer and a third alloy layer which are sequentially stacked, the first alloy layer and the third alloy layer are both Ag-Cu-Zn-Sn alloy, and the second alloy layer is Cu-Zn-Ni alloy; The Ag-Cu-Zn-Sn alloy comprises, in terms of mass percentage, Cu 35% to 45%, Zn 30% to 40%, Sn 0.5% to 5%, and Ag the balance; The Cu-Zn-Ni alloy comprises, in terms of atomic percentage, Zn 35% to 39%, Ni 1% to 9%, and Cu the balance.
2. The gradient composite filler material of claim 1, wherein The total thickness of the gradient composite filler is 180-260µm; And / or, the thickness ratio of the first alloy layer, the second alloy layer and the third alloy layer is 5-8:8-10:5-8.
3. The method of producing the gradient composite filler material according to claim 1 or 2, characterized by, The method comprises the following steps: S1. An alloy block is prepared by melting and casting with Ag, Cu, Zn and Sn as raw materials, and the alloy block is processed into a foil shape to obtain a first alloy foil and a third alloy foil; an alloy block is prepared by melting and casting with Cu, Zn and Ni as raw materials, and the alloy block is processed into a foil shape to obtain a second alloy foil; S2. The first alloy foil, the second alloy foil and the third alloy foil are compounded together in the order of "first alloy foil-second alloy foil-third alloy foil" to obtain a three-layer gradient structure.
4. The method of producing a gradient composite filler material according to claim 3, wherein At least one of the following characteristics is met: (1) In step S1, the processing step comprises rolling and / or wire cutting, and further comprises grinding; (2) The thickness of the first alloy foil and the third alloy foil is 50-80µm; (3) The thickness of the second alloy foil is 80-100µm; (4) In step S2, the compounding process is a resin bonding process.
5. Application of the gradient composite filler of claim 1 or 2 or the filler prepared by the method of claim 3 or 4 in welding of nickel-based high-temperature alloy.
6. A method of welding a GH4169D alloy, characterized by, The method comprises the following steps: A GH4169D alloy and a brazing material are assembled in the order of "GH4169D alloy-brazing material-GH4169D alloy" to obtain an assembly, and then vacuum brazing is performed; The brazing material is the gradient composite filler of claim 1 or 2 or the filler prepared by the method of claim 3 or 4.
7. The method of welding a GH4169D alloy of claim 6, wherein, The process of the vacuum brazing comprises: first vacuumizing, then heating to 350-450℃ at a first heating rate, then applying a pre-load of 8-12MPa to the assembly for first holding; after the holding, reducing the load to 4-6MPa, heating to a welding temperature at a second heating rate for second holding; after the holding, removing the pressure and cooling.
8. The method of welding a GH4169D alloy of claim 7, wherein, The first heating rate is 8-12℃ / min; and / or, the second heating rate is 8-12℃ / min.
9. The method of welding a GH4169D alloy of claim 7, wherein, The first holding time is 20-40min; and / or, the second holding time is 30-60min.
10. The method of welding a GH4169D alloy according to any one of claims 6 to 9, characterized in that, The welding temperature of the vacuum brazing is 860-890℃.